Does minimalist transfemoral transcatheter aortic valve replacement produce better survival in patients with severe chronic obstructive pulmonary disease?. Issue 4 (12th November 2016) - Condado, Jose F.; Haider, Moosa N.; Lerakis, Stamatios; Keegan, Patricia; Caughron, Hope; Thourani, Vinod H.; Devireddy, Chandan; Leshnower, Bradley; Mavromatis, Kreton; Sarin, Eric L.; Stewart, James; Guyton, Robert; et al.
Abstract : Objectives: To compare outcomes after minimalist and standard transfemoral transcatheter aortic valve replacement (TF‐TAVR) in patients with severe chronic obstructive pulmonary disease (COPD). Background: TF‐TAVR is increasingly performed with conscious sedation and transthoracic echocardiography guidance (minimalist). The safety/efficacy of this technique in patients with severe COPD is unknown. Methods: We compared demographics, 30‐day outcomes and 1‐year survival of patients with severe COPD (FEV1% ≤50) who underwent minimalist vs. standard TF‐TAVR between 2008 and 2015 at our institution. Results: Of 88 patients with severe COPD, 46 underwent minimalist and 42 underwent standard TF‐TAVR. There were no differences on baseline characteristics, except for more history of coronary artery bypass grafting (45.5% vs. 20.6%, P  = 0.03) and less history of cerebrovascular disease (16.7% vs. 45.5%, P  = 0.03) in the standard TF‐TAVR. Seventeen minimalist TF‐TAVR patients (41.0%) were transferred directly to the general medical ward with telemetry monitoring (without ICU stay); all standard TF‐TAVR patients went to the ICU. Minimalist TF‐TAVR patients had shorter procedure time (97 vs. 129 min, P  < 0.001), ICU time (21.8 vs. 29.8 hr, P  = 0.001) and length of stay (2 vs. 5 days, P  = 0.001). There were no differences in procedure complications and 30‐day mortality between groups. In our multivariate analysis, minimalist TF‐TAVR (HR 0.28, 95%CI 0.08–0.97) and previous coronary revascularization (HR 0.24, 95%CI 0.09–0.65) were associated with increased 1‐year survival. In contrast, moderate paravalvular leak (HR 7.73, 95%CI 1.94–30.84) was associated with decreased 1‐year survival. Conclusion: In patients with severe COPD, Minimalist TF‐TAVR results in less resource utilization and improved 1‐year survival compared to standard approach. Our findings should be validated in a larger cohort of patients with severe COPD. © 2016 Wiley Periodicals, Inc.